Strategic networks and entrepreneurial ventures - Stuart, Toby E.; Sorenson, Olav (Strategic Entrepreneurship Journal, 2007)
Abstract Much research suggests that social networks shape the emergence and development of nascent ventures. Scholars have argued that founders' and firms' networks influence innovation and the identification of entrepreneurial opportunities, as well as facilitate the mobilization of resources for growth and the harvesting of value from fledgling firms. It is not an exaggeration to claim that existing empirical findings point to the centrality of networks in every aspect of the entrepreneurial process. However, with exceptions so few they may be counted on one hand, this research untenably treats network structures as exogenous—in other words, as if entrepreneurs and enterprises do not pursue valuable connections. In this article, we review the literature on networks in entrepreneurial contexts, argue that it disproportionately focuses on the consequences of networks at the expense of research on their origins, and consider the implications for the literature of the fact that most entrepreneurs and young ventures are strategic in their formation of relations. We then articulate a research agenda composed of five areas of inquiry we consider critical to a better understanding of networks and entrepreneurship. Copyright © 2008 Strategic Management Society.